Outcome of Male Circumcision - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Circumcision is the surgical removal of the skin covering the glans penis (prepuce). Circumcision is performed worldwide, among many tribe and races. It is the commonest surgical procedure done in males. It is perform by both trained and non-trained medical personal.Aims and Objective:To compare the outcome of circumcision done by dorsal slit and plastibell methods.Methods and Materials:A prospective study was done over 1 year period. A structured questionnaire was used to collect data. It was a cross-sectional analytical study with sample size of 120 patients divided in to 2 study groups. Group A had dorsal slit while group B had plastibell type of circumcision.Results:The age of circumcision varies between 7days to 10 years. The average duration of the procedure was 12minutes for dorsal slit and 7 minutes, with estimated blood loss of 7mls and 4mls in the two methods. The most common complications observed in our study are surgical site infection, post operative haemorrhage, and delayed separation of the ring. While surgical site infection is more in plastibell method, post operative haemorrhage was found to be commoner in dorsal slit method.Conclusion:Our study showed that plastibell has an obvious advantage of shorter time of procedure, lower risk of post operative bleeding compared to the conventional dorsal slit method of circumcision.